Antinuclear antibodies in healthy people: the tip of autoimmunity's iceberg? - Pisetsky, David S (BioMed Central, 2011)
Antinuclear antibodies (ANAs) are venerable biomarkers for assessing the diagnosis and prognosis of patients with autoimmunity. While closely associated with diseases such as systemic lupus erythematosus, ANA expression occurs commonly in healthy people. The basis for this expression is unknown, although it may reflect features of the assays for antibody detection or intrinsic immunological disturbances in otherwise normal individuals. Like autoimmunity itself, ANA expression is more common among women than men, pointing to an important determinant of these responses. Future research will clarify the mechanisms of ANA expression and the utility of current assays as antecedent and screening biomarkers.